Giving in dictator games: regard for others or regard by others? - Alexander K. Koch; Hans-Theo Normann (Institute for the Study of Labor (IZA), 2005)
Recent bargaining experiments demonstrated an impact of anonymity and incomplete information on subjects' behavior. This has rekindled the question whether fair behavior is inspired by regard for others or is explained by external forces. To test for the importance of external pressure we compare a standard double blind dictator game to a treatment which provides no information about the source of dictator offers, and where recipients do not even know that they participate in an experiment. We find no differences between treatments. This suggests that those dictators who give are purely internally motivated, as asserted by models of other-regarding preferences.
Keywords: A13; C91; D64; 330; dictator game; altruism; social preferences; Altruismus; Spieltheorie; Test